Design of Mobile Learning Application Interface Using Kansei Engineering Method (Case Study: Majelis Daur Ulang) - Imam Maruf Nugroho; Yudhi Raymond Ramadhan; Ibrahim Aljaedi (Universitas Negeri Padang, 2026)
Kansei Engineering is a method for realizing certain product designs based on a systematic exploration of human feelings and sensations (sight, touch, smell, hearing, taste). In mobile applications, the most important factor apart from the technical aspects of the system is the design. Design is an important factor in a mobile application because it becomes a liaison between the user and the existing system. The Mobile Learning application is not only enough to run the application and there are no errors, but the application must be built according to the wishes and interests of the user, this study aims to determine the emotional factors of the user, apply Kansei Engineering in designing and make recommendations for application display design according to Kansei Engineering. This methodology refers to Kansei Engineering Type I. This study uses Kansei Word to detect the user's feelings when looking at the specimen design. The list of Kansei Words used is 10 words related to the Majelis Daur Ulang mobile learning application. There are 5 specimens of similar Mobile Learning applications used. This study involved 32 participants, using multivariate statistical analysis, namely Cronbach's Alpha (CA), Correlation Coefficient Analysis (CCA), Principal Component Analysis (PCA), Factor Analysis (FA) and Partial Least Square (PLS). This research resulted in 2 recommendations for the design Majelis Daur Ulang Mobile Learning display, namely